Mitigating risk: Social protection and the rural poor - Kanbur, Ravi (International Food Policy Research Institute, 2015)
People in developing countries—particularly the agricultural poor—face a host of risks to their lives and livelihoods, including those stemming from globalization, climate change, and weather shocks. These experiences highlight the importance of social protection, which can have a potentially significant impact on reducing poverty and vulnerability when implemented with the optimal design, targets, and resources.